2002
DOI: 10.1002/elps.200290032
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of human liver tumor tissue by two‐dimensional gel electrophoresis and matrixassisted laser desorption/ionization‐mass spectrometry for identification of disease‐related proteins

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy worldwide and is a leading cause of death. To contribute to the development and improvement of molecular markers for diagnostics and prognostics and of therapeutic targets for the disease, we have largely expanded the currently available human liver tissue maps and studied the differential expression of proteins in normal and cancer tissues. Reference two-dimensional electrophoresis (2-DE) maps of human liver tumor tissue include labeled 2-DE images for tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 37 publications
(21 reference statements)
10
70
0
Order By: Relevance
“…These data suggest that overexpression of NF-jB associated Wnt-1 protein might be an important mechanism of hepatocarcinogenesis common to HBV and HCV infection. Several studies have reported proteomic analysis of HCC, either from tumor tissues [29,32,33], or from patients' sera [34]. All these studies attempted to identify specific factors correlated with hepatocarcinogenesis or novel tumor markers for early diagnosis of HCC, but these goals seem far from reach [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that overexpression of NF-jB associated Wnt-1 protein might be an important mechanism of hepatocarcinogenesis common to HBV and HCV infection. Several studies have reported proteomic analysis of HCC, either from tumor tissues [29,32,33], or from patients' sera [34]. All these studies attempted to identify specific factors correlated with hepatocarcinogenesis or novel tumor markers for early diagnosis of HCC, but these goals seem far from reach [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Tryptic peptides from 2-DE protein spots were subjected to peptide mass fingerprinting (PMF) using a matrix-assisted laser desorption/ionization quadrupole-time of flight (MALDI-Q-TOF) mass spectrometer (M@LDI TM ; Micromass, Manchester, UK) operated in reflectron positive ion mode as described [27][28][29]. Briefly, samples were spotted onto the 96-well format MALDI target plate using a saturated matrix solution of a-cyano-4-hydroxycinnamic acid (CHCA) in 60% ACN/1% TFA.…”
Section: Mass Spectrometric Analysismentioning
confidence: 99%
“…Consequently, molecular biomarkers associated with HCC should be identified. Different proteomics have been applied to the study of HCC, resulting in panels of altered proteins that are proposed as markers with key roles in the progression of the disease in certain cases (28)(29)(30)(31)(32)(33)(34)(35). However, the protein repertoires reported in these studies are barely coincident and, consequently, their value as biomarkers for HCC is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, SELDI-TOF-MS has been successfully applied in many types of tumors. A number of biomarkers in this process have been identified and further characterized, associated with cancers such as breast (16)(17)(18), liver (19)(20)(21), lung (22,23), prostate (24) and ovarian cancers (25). These studies suggest that SELDI-TOF-MS ProteinChip technology can distinguish cancer patients from normal subjects with relatively high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%